Strategi Komunikasi Binluh Penyuluh Agama Hindu Kementerian Agama Kota Denpasar dalam Meningkatkan Sraddha dan Bhakti Masyarakat Hindu di Kota Denpasar - Ratih, Ida Ayu; Relin D.E; I Nyoman Ananda (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
Before the Covid-19 pandemic, Hindu extension workers conducted face-to-face coaching for the community. However, after the Covid-19 pandemic, community formation has been disrupted due to regulations from the government that prohibit gathering with large numbers of people. In the midst of changes in communication media in this new normal era, of course, there are difficulties in implementing counseling through video. Is there a significant difference in the increase of Hindu Sraddha and Bhakti if guidance and counseling (Binluh) are carried out through videos shared through social media. Therefore, researchers are interested in further studying the phenomenon so that it is poured in a scientific paper entitled "Communication Strategy for Hindu Extension Binluh Ministry of Religious Affairs of Denpasar City in Improving Sraddha and Bhakti Hindu Community in Denpasar City". The theories used in this study are Foucault's theory, symbolic interaction theory, and persuasive communication theory. This research is a qualitative research with a type of positivism research. The location of this study is at the Ministry of Religious Affairs of Denpasar City. The types and sources of data used are primary and secondary data. The informant determination technique is purposive sampling. Data collection techniques include observation, interviews, literature studies, and document studies. The findings of the research are: (1) The Binluh System carried out by the Hindu Extension Officer of the Ministry of Religious Affairs of Denpasar City includes planning, implementation and evaluation; and (2) Hindu Extension Officer of the Ministry of Religious Affairs of Denpasar City through verbal and nonverbal communication processes.